2019
DOI: 10.3390/cancers11091337
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Oncogenic Drivers in 3D Cell Culture Depends on Nuclear ATP Synthesis by NUDT5

Abstract: The growth of cancer cells as oncospheres in three-dimensional (3D) culture provides a robust cell model for understanding cancer progression, as well as for early drug discovery and validation. We have previously described a novel pathway in breast cancer cells, whereby ADP (Adenosine diphosphate)-ribose derived from hydrolysis of poly (ADP-Ribose) and pyrophosphate (PPi) are converted to ATP, catalysed by the enzyme NUDT5 (nucleotide diphosphate hydrolase type 5). Overexpression of the NUDT5 gene in breast a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…Wright et al (2016) found that progestin or estrogen-induced nuclear ATP increasing, chromatin remodeling, and gene transcription changes are dependent on the activity of NUDT5 in breast cancer cell lines T47D and MCF7. NUDT5 was also found to be overexpressed in breast cancer patients and is correlated with a poorer prognosis and a higher risk of recurrence and metastasis (Pickup et al, 2019). These findings revealed the important role NUDT5 played in the estrogen signaling pathway and that it is thus involved in the pathogenesis of breast cancer.…”
Section: Introductionmentioning
confidence: 76%
“…Wright et al (2016) found that progestin or estrogen-induced nuclear ATP increasing, chromatin remodeling, and gene transcription changes are dependent on the activity of NUDT5 in breast cancer cell lines T47D and MCF7. NUDT5 was also found to be overexpressed in breast cancer patients and is correlated with a poorer prognosis and a higher risk of recurrence and metastasis (Pickup et al, 2019). These findings revealed the important role NUDT5 played in the estrogen signaling pathway and that it is thus involved in the pathogenesis of breast cancer.…”
Section: Introductionmentioning
confidence: 76%
“…Indeed, complex components IKKα, RelB and p52 are associated with decreased cancer-specific survival in ERa-positive breast cancer (Paul et al, 2018). This may be linked to the cancer stem cell niche, which we showed recently was present in T47D cells grown in 3D cultures (Pickup et al, 2019).…”
Section: Specific Pathways: Roles Of Ampk Insulin Tnfa and Pik3mentioning
confidence: 55%
“…fragments and the immunogold particles accumulate in the border between this dispersed chromatin and the nucleoplasm (Perrot-Applanat et al 1986). The recent advances in high resolution microscopy and single molecule tracking will be key for exploring the dynamics of nuclear phase transitions in living cells.…”
Section: Figurementioning
confidence: 99%
“…The availability of NUDIX5 specific inhibitors ( Page et al 2018 ) will help to clarify these processes in more sophisticated biological models, including 3D cell cultures and mouse intraductal xenografts ( Sflomos et al 2016 ). We have recently found that nuclear synthesis of ATP by NUDIX5 is essential for the formation of oncospheres by breast cancer cells grown in 3D cultures, due to the dependence of the cancer stem cells on nuclear ATP ( Pickup et al 2019 ). As NUDIX5 is overexpressed in breast tumors and correlates with poor prognosis ( Wright et al 2016 ), it represents a novel possible target for the pharmacological control of cancer growth.…”
Section: Role Of Nuclear Atp Synthesismentioning
confidence: 99%